Agronomic And Biochemical Expression Of Salt Stress In Iranian Rice Cultivars - Momayezi, Mohammad Reza (2010)

(untitled)
Salinity stress is a complex effect causing an external osmotic potential to prevent water uptake, an inhibitory specific-ion effect such as Na+, Cl- on plant metabolism and nutrient imbalance in stressed plants. Therefore tolerance of a plant to salinity stress should contain the ability to overcome the osmotic challenge and alleviate ion toxicity. Plants show different responses to salt stress at the molecular, cellular and whole plant levels. The capacity to tolerate salinity can be a key factor in rice productivity. It is generally accepted that proline as a common osmolytes was accumulated under salinity condition to conserve osmotic stability and to prevent damage however the role of proline in osmotic adjustment is still being debated. Mechanisms avoidance and tolerance against salinity stress support this idea that these mechanisms constitute a significant aspect of salt tolerant in rice. Therefore our study explored the defense mechanism of rice at different growth stages (germination, seedling and reproductive stages) that contribute to salt tolerance in rice. The concentration and composition of solutes in the soil solution are usually very different. Thus this study was carried out to investigate the rice response to salt composition and concentration under a saline soil solution. Therefore the general hypothesis here is that amino acids accumulation as a defense mechanism may be affected by changing in the salt compositions and concentrations. Eleven widely grown rice cultivars in Iran were selected for this study. These are Pouya, Shafag, Neda, Kadous, Tabesh, Tarom-e-Hashemi, Sahel, Khazar, Shirodi, Fajr and Nemat and the relationship between the physiological and biochemical parameters; root characteristics, shoot height, dry weight, water content percentage and free amino acids status as affected by salt concentrations and composition were determined at the different rice growth stages. The root of rice seedlings were scanned by WINRHIZO system. Proline content was measured by acid - ninhydrin method. The elements (K, Ca, Mg and Na) were measured by dry ashing method and inductively coupled argon-plasma emission spectrometry (ICP trace analyzer). The free amino acids were separately determined in shoot and root by HPLC system. Quality of suberin in the lamella of roots was determined by staining of free-hand section. The sections were examined using a light microscope (Olympus bx51, Olympus and Melville, NY, USA). At germination stage, the results revealed that (1) the mean germination time (MGT) was positively affected by increasing salt concentration. Conversely, a negative relationship between germination index (GI) and salt concentration was recorded; (2) a significant difference between germination parameters and salt compositions was observed and (3) there was non-significant correlation between proline and water content. The analyzed data at seedling and reproductive stages showed that (1) the root length, root surface area, shoot height and dry weight of root and shoot as the physiological parameters were reduced by increasing salinity levels, (2) the relationship between the root surface area and salt compositions was not significantly (p ≤0.01) observed; (3) the interaction between salt concentration and composition was mostly significant (p ≤0.01); (4) a significant reduction in K+/Na+, Ca2+/Na+ and Ca2++Mg2+/Na+ ratios in seedlings when salinity level was increased was recorded; (5) the free amino acids in root did not show significant differences. However free amino acids in shoot were significantly (p ≤0.05) increased as salt concentration increased; (6) Aspartic acid can be susceptible and reliable indicator for osmotic adjustment in the rice shoot, at least in these rice genotypes (7) salt composition intensify suberin development and (8) yield components were affected by salt concentration more than salt composition. It can be concluded that (A) aspargine as a compatible solute was involved in osmotic adjustment; (B) these rice cultivars were not able to compartmentalize Na+, K+ and Ca2+ in their seedling segments (C) Fajr as a salt tolerant cultivar regulated suberization more than that observed in salt sensitive Khazar and (D) the anion associated with Na were more effective at seedling stage than at germination or reproductive stages.